ATIM-07. EFFICACY AND SAFETY OF NIVOLUMAB IN PATIENTS WITH FIRST RECURRENCE OF GLIOBLASTOMA: A MULTICENTER, OPEN-LABEL, NON-COMPARATIVE STUDY (ONO-4538-19). (11th November 2019) - Kagawa, Naoki; Aoki, Tomokazu; Sugiyama, Kazuhiko; Wakabayashi, Toshihiko; Arakawa, Yoshiki; Yamaguchi, Shigeru; Tanaka, Shota; Nishikawa, Ryo
Abstract: BACKGROUND: The anti-programmed cell death protein 1 (PD-1) immune checkpoint antibody, nivolumab, may be beneficial in patients with recurrent glioblastoma. OBJECTIVE: This open-label, non-comparative study assessed the efficacy and safety of nivolumab in Japanese patients with first recurrence of glioblastoma. METHODS: Patients with a first recurrence of histologically confirmed World Health Organization (WHO) Grade IV glioma, after treatment with temozolomide plus radiotherapy, received nivolumab 3 mg/kg every 2 weeks until confirmed disease progression based on Response Assessment in Neuro-Oncology (RANO) criteria or development of toxicity. The primary endpoint was 1-year overall survival rate (1y-OS) assessed using a Bayesian approach. The prespecified efficacy criteria were that the Bayesian posterior mean 1y-OS with nivolumab would be 49%, and the Bayesian posterior probability threshold for exceeding the 1y-OS of bevacizumab (34.5%) from the Japanese Phase II study (JO22506) would be 93%. RESULTS: Of the 50 patients enrolled, 44 (93.5%) had recurrent malignant glioma (glioblastoma and gliosarcoma), 26 (59.1%) had measurable disease, and 4 (9.1%) received corticosteroids at baseline. The posterior mean (90% Bayesian credible intervals) 1y-OS with nivolumab was 54.35% (42.27–66.21), and the observed posterior probability of exceeding the 1y-OS of bevacizumab (34.5%, JO22506) was 99.7%. The median (90% confidence interval) overall and progression-free survival (PFS) was 13.09 months (10.38, 17.68) and 1.45 months (1.41, 1.54), respectively. One partial response was observed (objective response rate [ORR] 1/26 evaluable patients [3.8%]). The grade 3–5 treatment-related adverse event rate was 16.0%; most adverse events resolved and were manageable. CONCLUSION: The 1y-OS with nivolumab monotherapy in Japanese patients was higher than that in the bevacizumab group in the JO22506 study. However, PFS and ORR were not improved compared with JO22506. The safety profile of nivolumab was consistent with that observed in other tumor types.